2021
DOI: 10.24127/ajpm.v10i2.3635
|View full text |Cite
|
Sign up to set email alerts
|

Pegaruh Pembelajaran Daring Dengan Google Classroom Dan Google Meet Terhadap Minat Belajar Matematika Diskrit

Abstract: Tujuan dari penelitian ini adalah untuk mengetahui pegaruh pembelajaran daring dengan google classroom dan pengaruh pembelajaran darng dengan google meet terhadap minat belajar mahasiswa pada mata kuliah matematika diskrit serta untuk mengetahui pengaruh pembelajaran daring dengan google clasroom dan google meet secara bersama-sama terhadap minat belajar matematika diskrit. Metode penelitian yang digunakan adalah kuantitatif. Teknik pengambilan sampel pada penelitian ini adalah menggunakan Simple Random Sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…According to (Riduwan, 2003) simple random sampling is a way of taking samples from members of the population at random without paying attention to the strata / levels in the population members. Determination of the number of samples using the Slovin formula (Putri & Kartika, 2017;Wahyuniar et al, 2021). From the calculation using the formula, the sample used in this study was 56 students.…”
Section: Methodsmentioning
confidence: 99%
“…According to (Riduwan, 2003) simple random sampling is a way of taking samples from members of the population at random without paying attention to the strata / levels in the population members. Determination of the number of samples using the Slovin formula (Putri & Kartika, 2017;Wahyuniar et al, 2021). From the calculation using the formula, the sample used in this study was 56 students.…”
Section: Methodsmentioning
confidence: 99%
“…Hasil belajar merupakan salah satu tujuan pembelajaran, yang artinya salah satu tujuan pembelajaran terpenuhi dengan menggunakan media google classroom, maka pembelajaran daring dengan memanfaatkan google classroom dapat dikatakan efektif diterapkan saat pandemi covid 19 di SMA Negeri 02 Bengkulu Utara. Hal ini sependapat dengan hasil penelitian Wahyuniar (2021) bahwa pembelajaran daring dengan google classroom dan pembelajaran daring dengan google meet secara bersama-sama mempunyai pengaruh sebesar 55% terhadap minat belajar matematika diskrit, sedangkan sisanya 45% dipengaruhi oleh variabel di luar penelitian ini. Penelitian ini melihat efektifitas pembelajaran dari minat dan hasil belajar dan kita ketahui banyak indikator lainnya yang dapat digunakan untuk melihat efektifitas pembelajaran dan dapat dilakukan oleh peneliti pada penelitian selanjutnya.…”
Section: Efektivitas Pembelajaranunclassified
“…Research conducted by Wahyuniar et al (2021) has 4 indicators of interest in learning, namely feelings of pleasure in learning, concentration of attention and learning thoughts, willingness to learn, willingness from within to actively learn. Friantini and Winata (2019) states that there are 5 indicators of student interest in learning, namely 1) feelings of pleasure towards learning, 2) concentration of mind and attention in the learning process, 3) willingness to learn, 4) willingness from within to learn actively, 5 ) efforts made to realize the desire to learn.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by Wahyuniar et al (2021) found that online learning has an influence on students' interest in learning in discrete mathematics courses. Research that has been conducted by Putra, Juniawan, and Atzmi (2021) shows that students' interest in learning is higher when learning is done offline than online.…”
Section: Introductionmentioning
confidence: 99%